Pengaruh information dan communication technology adoption serta digital transformation terhadap asset growth UMKM - Revolino Hardi; Agus Zainul Arifin (Universitas Tarumanagara, 2023)
In the current era of the digital industry, the use of information technology supports a business sector in marketing its products. One of the information technologies that is widely used by MSME actors is the use of social media in conveying information. The purpose of this study was to examine the relationship between the Adoption of Information and Communication Technology (ICT) and Digital Transformation Understanding of business opportunities so that it has an impact on MSME asset growth with a descriptive analysis method using a collection of 117 respondents. The results obtained in this study are that there is no relationship between the adoption of information and communication technology on the growth of SME assets. This is because MSME owners are only aware of the importance of using new technology but have not fully used new technology in their businesses, while SME asset growth is more influenced by an understanding of digital transformation by SMEs. Di dalam era industri digital saat ini, penggunaan teknologi informasi menjadi penopang suatu bidang usaha melakukan pemasaran produknya. Salah satu teknologi informasi yang ramai digunakan oleh pelaku UMKM adalah penggunaan media sosial dalam penyampaian informasi. Tujuan dari penelitian untuk mengkaji keterkaitan antara Adopsi Teknologi Informasi dan Komunikasi (TIK) dan Pemahaman Transformasi Digital atas peluang bisnis sehingga berdampak pada pertumbuhan aset UMKM dengan metode analisa deskriptif menggunakan pengumpulan responden sebanyak 117 responden. Hasil yang diperoleh pada penelitian ini adalah tidak ada keterkaitan antara adopsi teknologi informasi dan komunikasi terhadap pertumbuhan aset UMKM. Hal ini dikarenakan bahwa para pemilik UMKM hanya sebatas sadar akan pentingnya penggunaan teknologi baru namun belum sepenuhnya menggunakan teknologi baru pada usaha mereka sedangkan pertumbuhan aset UMKM lebih dipengaruhi oleh pemahaman akan transformasi digital oleh para pemilik UMKM.